BERAT DAN PANJANG BAYI SERTA NILAI Z SKORBAYI DENGAN ASI PREDOMINAN DAN PARSIAL BERDASARKAN STANDAR WHO 2005 DAN NCHS - Anies Irawati; Endang L. Achadi; Abas B Jahari (PERSATUAN AHLI GIZI INDONESIA, 2008)
New WHO standard introduce to implemented in every country including Indonesia. Thepopulation of children to develop new standard comes from good economic status and lowmobility. Three quarters infant were exclusive/predominantly breastfed for at least four month. InIndonesia, predominantly and partially breastfed most practiced than exclusive breastfeeding. Tocompare the growth of infantsaccording to WHO new standard and NCHSreference. Methods:Analyzed using secondary data of cohort prospective research of “the influence earlysupplementation infant feeding to first four month infant growth”. Developing curve of infant weightand length attainment for predominant and partially breastfed; also developing curve Z score(weight for age, weight for length and length for age) for predominant and partially breastfed. Bothcurves development are using new WHO standard and NCHS reference. During the first fourmonth, the weight and length deviation of infant with predominantly and partially breastfed usingnew who standard larger than NCHS, and infant with predominantly breastfed better than partiallybreastfed. The Z score curve for weight for age, length for age and weight for age simultaneouslyas a pattern of new WHO standard, but since birth until 4 month age the number of Z score forthose indicators lower than WHO new standard. New WHO standard anthropometry morerepresentative to infant growth than NCHS reference.Keywords: Predominant breastfed infants, partially breastfed infants, growth curve, New WHOstandard, NCHSreference